Changing patterns of privatization: Ideology, economics necessity, or political opportunism - Colley, Linda Katurah; Head, Brian (2013)
This article considers privatization decisions by governments in four Australian states over twenty years of micro-economic reform. It focuses on the policy frameworks and political context for privatizing government enterprises, drawing on Kingdon's framework for policy change to analyze differences in the substance and timing of decisions. In the 1990s, governments considered privatization as an economic and political strategy to resolve the problem of state-level fiscal crises, but the patterns of adoption were variable. Two states resisted the general trend toward privatization, but recently changed their position. We argue that the recent financial crisis provided a window for reintroducing contentious reform initiatives that had lost momentum. - Reproduced.
Keywords: Privatization